Manajemen Pengelolaan Barista (Caffe Shop): PKBM Syafa’at Kecamatan Pagerbarang Kabupaten Tegal - Mirza Anindya Pangestika; Nurul Wulandari Putri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The growing demand for coffee drinks has created significant opportunities in the coffee shop sector, especially for young people. However, in the Pagerbarang Kabupaten Tegal area, the majority of young people still lack the skills needed to professionally run a coffee business or the technical abilities of a barista. In response to this situation, this community service activity was implemented with the aim of providing training in coffee shop management and basic barista skills to increase the competitiveness of young people in the creative economy sector. This training was developed through a participatory approach integrating interactive classes for understanding theory, direct practice for skill acquisition, and support in developing a business plan as a first step towards entrepreneurship. This activity revealed an increase in participants' skills and understanding of coffee shop management and operations, customer relations, and fundamental coffee service skills. Participants also expressed a strong interest in starting their own businesses. This initiative is expected to serve as a catalyst for encouraging an entrepreneurial spirit among young people and contributing to the sustainable development of the local economy